Long-term stability of NH3-SCR catalysts in the presence of high NO2 concentrations and the performance of a modified V-W-Mo catalyst - Bo Yu; Qichao Li; Shuran Zhou; Heng Yang; Xingyu Liu; Hanjun Lu; Zhongwei Wang; Li Yang; Fang Liu (Fuel, 2027)

Efficient electrocatalytic reduction of nitrate to ammonia over oxygen vacancy-rich copper - Shixuan Zhan; Cong Yan; Yang Tang; Yuanhao Wang; Xiao Jin Yang; Hanjun Hu (Journal of Environmental Chemical Engineering, 2026)

Hydrothermal humic acid formation from pine bark, sugarcane bagasse, and Spirulina: A comparative mechanistic study on lignin-, holocellulose-, and protein-rich biomass - Libo Zhang; Ziying Zhang; Hui Wang; Yaxiong Ji; Hanjun Hu (Chemical Engineering Journal, 2026)

Hyp-retro: hypernetwork-guided preference-conditioned retrosynthetic planner - Jingwen Wang; Shuan Liu; Shaoye Zhang; Jianbo Qiao; Guanhe Li; Hanjun Zhao; Xiangxiang Zeng; Jinjin Li; Changhang Lin; Chen Su; Leyi Wei (Molecular Diversity, 2026)

Compartmentalization of heavy metal content, speciation and ecological risks in sludge electro-dewatering: Role of hydroxycarboxylate chelating agents −extracellular polymeric substances −heavy metals interactions - Bingdi Cao; Song Huang; Hanjun Wu; Tao Zhang; Dongsheng Wang (Bioresource Technology, 2026)

Csp-π-d conjugation engineering strategy for optimizing *OH intermediate regulation of reinforced oxygen reduction reaction - Yang Lu; Yimin Mou; Ziyang Jia; Yiyi Fan; Lei Cheng; Yawen Tang; Yafei Li; Yu Wang; Hanjun Sun (Science Bulletin, 2026)

Improving porcine meat quality during freezing with agaro-oligosaccharide and pigskin collagen peptides: A study on ice recrystallization and myofibrillar proteins structure - Mingming Zhu; Ketao Chen; Wang Liu; Lijie Jiang; Hanjun Ma; Hui Wang; Zhuangli Kang (Food Chemistry, 2026)

Larix gmelinii growth limitation shifts from nitrogen availability to drought under warming and permafrost degradation - Zecheng Chen; Binqing Zhao; Wenqi Song; Hans W. Linderholm; Jan Altman; Keyu Zhang; Hanjun Dong; Xinran Huang; Haoyuan Chen; Xiaochun Wang (Global and Planetary Change, 2026)

Mechanism of enhancing nitrogen removal by iron-modified biochar in anammox treatment of ammonia nitrogen wastewater from rare earth mines - Xiangyi Deng; Shengnan Huang; Zhenyue Zhang; Hanjun Wu; Liqi Chai; Xiang Ma; Anfu Wang (Process Safety and Environmental Protection, 2026)

Polyamide microplastics outperform polylactic acid in reducing cadmium health risks in arsenic-cadmium co-contaminated water: Insights from experimental and theoretical analysis - Zelin Xu; Xiyan Jiang; Jingnan Ma; Pengfei Wang; Peng Xiao; Nan Yang; Damao Xu; Shibo Yan; Hanjun Zhu; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2026)

Nitrogen-doped porous biomass-derived carbons for enhanced hydrophobicity, microwave absorption and thermal insulation - Siyu Chen; Zhiyong Chen; Lu Tang; Jimei Xue; Zhijun Wang; Ying Li; Hanjun Wei (Fuel, 2026)

High internal phase emulsions co-stabilized by rutin and grass carp myofibrillar protein: Multi-scale mechanism analysis based on interface protein composition and molecular dynamics - Xuehua Zhang; Mengke Li; Benguo Liu; Hao Zhang; Hui Wang; Wenzheng Shi; Hanjun Ma (Food Research International, 2025)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

Design of BNT-based ceramics with enhanced energy density and ultrahigh polarization under moderate electric field via introducing BMW - Pan Gao; Wenjing Geng; Chang Liu; Hanjun Wang; Yun Ling; Yubo Li; Hongyan Wan; Haijuan Li; Xincheng Ren (Chemical Engineering Journal, 2025)

How do board governance and operational management affect carbon emissions among full-service and low-cost carriers? - Huan Wang; Kan Wai Hong Tsui; Qingxia Jenny Wang; Hanjun Wu; Xiaowen Fu; Fan Hu (Journal of Cleaner Production, 2025)

Interaction mechanisms between microplastics and environmental endocrine disruptors during hydrothermal treatment of sludge - Hanjun Wu; Tianjun Liu; Qingrong Cheng; Hong Zhou; Zhiquan Pan; Bingdi Cao; Dongsheng Wang (Environment, Development and Sustainability, 2025)

Exploring the association between air pollution and urogenital congenital anomalies: a global ecological analysis - Kebin Chen; Hanjun Liu; Tingting Wang; Manjun Luo; Xiaorui Ruan; Mengting Sun; Ziye Li; Jianhui Wei; Jiabi Qin (Environmental Pollution, 2025)

Analysis of the influencing mechanism of low-frequency alternating magnetic field-assisted freezing on oxidative and structural attributes of pork myofibrillar proteins based on proteomic changes - Mingming Zhu; Lijie Jiang; Wang Liu; Huijie Li; Lingxia Jiao; Hanjun Ma; Xueli Gao; Zhuangli Kang (Food Chemistry, 2025)

Mixed surfactants with solubilization behaviors: Separation of feldspar and quartz by self-assembly flotation - Xuyang Fan; Tingting Xiao; Chenyu Zhou; Haoran Wang; Zhiquan Pan; Hanjun Wu; Hong Zhou (Minerals Engineering, 2025)

Oil/water interface behavior of hesperidin methylchalcone and its application in nano-emulsions - Yuxiang Wang; Benguo Liu; Yuling Ma; Chunyan Wang; Hanjun Ma; Sheng Geng (Food Chemistry, 2025)

Modulation of the conformation, water distribution, and rheological properties of low-salt porcine myofibrillar protein gel influenced by modified quinoa protein - Shengming Zhao; Liu Yang; Xiang Chen; Yanyan Zhao; Hanjun Ma; Hui Wang; Anxiang Su (Food Chemistry, 2024)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

Spatiotemporal evolution of air cargo networks and its impact on economic development - An analysis of China's domestic market before and during the COVID-19 pandemic - Hang He; Hanjun Wu; Kan Wai Hong Tsui; Biao Wang; Xiaowen Fu (Journal of Transport Geography, 2024)

Full-spectrum-responsive Ti4O7-PVA nanocomposite hydrogel with ultrahigh evaporation rate for efficient solar steam generation - Xinye Xu; Qi Zhao; Qi Liu; Junxiao Qiu; Jinhao Li; Wenqian Zheng; Jie Cao; Lina Wang; Wen Wang; Shutong Yuan; Anni Fu; Hanjun Yang; et al. (Desalination, 2024)

Enhanced energy-storage properties in (Bi0.5Na0.5)TiO3 ceramics by doping linear perovskite materials Ca0.85Bi0.1(Sn0.5Ti0.5)O3 - Pan Gao; Xinye Huang; Chang Liu; Rongjie Zhang; Hanjun Wang; Wenjing Geng; Zixiong Sun; Zenghui Liu; Xincheng Ren; Yongping Pu (Chemical Engineering Journal, 2024)

PKHD1L1, a gene involved in the stereocilia coat, causes autosomal recessive nonsyndromic hearing loss - Shelby E. Redfield; Pedro De-la-Torre; Mina Zamani; Hanjun Wang; Hina Khan; Tyler Morris; Gholamreza Shariati; Majid Karimi; Margaret A. Kenna; Go Hun Seo; Hongen Xu; Wei Lu; et al. (Human Genetics, 2024)
Identification of genes associated with nonsyndromic hearing loss is a crucial endeavor given the substantial number of individuals who remain without a diagnosis after even the most advanced genetic testing. PKHD1L1 was established as necessary for the formation of the cochlear hair-cell stereociliary coat and causes hearing loss in mice and zebrafish when mutated. We sought to determine if biallelic variants in PKHD1L1 also cause hearing loss in humans. Exome sequencing was performed on DNA of four families segregating autosomal recessive nonsyndromic sensorineural hearing loss. Compound heterozygous p.[(Gly129Ser)];p.[(Gly1314Val)] and p.[(Gly605Arg)];p[(Leu2818TyrfsTer5)], homozygous missense p.(His2479Gln) and nonsense p.(Arg3381Ter) variants were identified in PKHD1L1 that were predicted to be damaging using in silico pathogenicity prediction methods. In vitro functional analysis of two missense variants was performed using purified recombinant PKHD1L1 protein fragments. We then evaluated protein thermodynamic stability with and without the missense variants found in one of the families and performed a minigene splicing assay for another variant. In silico molecular modeling using AlphaFold2 and protein sequence alignment analysis were carried out to further explore potential variant effects on structure. In vitro functional assessment indicated that both engineered PKHD1L1 p.(Gly129Ser) and p.(Gly1314Val) mutant constructs significantly reduced the folding and structural stabilities of the expressed protein fragments, providing further evidence to support pathogenicity of these variants. Minigene assay of the c.1813G>A p.(Gly605Arg) variant, located at the boundary of exon 17, revealed exon skipping leading to an in-frame deletion of 48 amino acids. In silico molecular modeling exposed key structural features that might suggest PKHD1L1 protein destabilization. Multiple lines of evidence collectively associate PKHD1L1 with nonsyndromic mild–moderate to severe sensorineural hearing loss. PKHD1L1 testing in individuals with mild–moderate hearing loss may identify further affected families.

Evaluating the effects of low-frequency alternating magnetic field thawing on oxidation, denaturation, and gelling properties of porcine myofibrillar proteins - Mingming Zhu; He Wang; Jiaxing Zong; Juan Zhang; Shengming Zhao; Hanjun Ma (Food Chemistry, 2024)

Self-healing transparent ionogel polymerized by liquid metal for strain sensor - Siying Wang; Xuan Huang; Hanjun Sun; Fangfang Wang; Bing Lei; Wenjun Wang; Qian Wang; Ying Yang; Jinjun Shao; Xiaochen Dong (Chemical Engineering Journal, 2023)

Pd3Pb bimetallic aerogels for anti-poisoned oxygen reduction reaction - Hui Fu; Juan Wang; Yao Chen; Honggang Huang; Yang Wang; Hanjun Li; Feili Lai; Longsheng Zhang; Nan Zhang; Jiadong Chen; Tianxi Liu (Chemical Engineering Journal, 2023)

In-doping induced resonant level and thermoelectric performance enhancement in n-type GeBi2Te4 single crystals with intrinsically low lattice thermal conductivity - Peng Chen; Bin Zhang; Hanjun Zou; Xiangnan Gong; Yanci Yan; Jingwei Li; Daliang Zhang; Guang Han; Xu Lu; Hong Wu; Yun Zhou; Xiaoyuan Zhou; et al. (Chemical Engineering Journal, 2023)

Dissolved organic matter transformation mechanisms and process optimization of wastewater sludge hydrothermal humification treatment for producing plant biostimulants - Siying Cai; Yu Zhang; Aibin Hu; Ming Liu; Hanjun Wu; Dongsheng Wang; Weijun Zhang (Water Research, 2023)

Synthesis of honeycomb lignin-based biochar and its high-efficiency adsorption of norfloxacin - Hanjun Zhou; Zheng Wang; Chunli Gao; Qianqian Sun; Jing Liu; Diao She (Bioresource Technology, 2023)

Gene expression profile analysis indicate SEPALLATA3 and AGL15 potentially involved in arabidopsis silique dehiscence by regulating glycosyl hydrolase - Xingshan Jiang; Hanjun He; Ting Wang; Xiaojing Wang; Hong Wu (Journal of Plant Biology, 2016)

Physical-Chemical Properties of Collagens from Skin, Scale, and Bone of Grass Carp ( Ctenopharyngodon idellus ) - Haibo Wang; Yanping Liang; Haiyin Wang; Hanjun Zhang; Min Wang; Liangzhong Liu (Journal of Aquatic Food Product Technology, 2014)

Expressional profiling study revealed unique expressional patterns and dramatic expressional divergence of maize α-zein super gene family - Lingna Feng; Jia Zhu; Gang Wang; Yuanping Tang; Hanjun Chen; Weibo Jin; Fei Wang; Bing Mei; Zhengkai Xu; Rentao Song (Plant Molecular Biology, 2009)